2021
DOI: 10.4103/wjnm.wjnm_74_20
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the survival benefit of completing all the six cycles of radium-223 therapy in patients with castrate-resistant prostate cancer with predominant bone metastases

Abstract: A retrospective analysis was performed of epidemiological data assessing the survival of patients who had received radium-223 for castrate-resistant metastatic prostate cancer treated at a regional tertiary referral center over a 5-year period. The patients' age, date of first treatment, and the number of cycles of radium-223 given were obtained from the patients' electronic patient record (EPR). Data on the date of death were provided by national death registrations which update the EPR via a unique national … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…In the present analysis, we verified whether the prognostic power of the BIO-Ra score is still preserved in light of the EMA restriction of the use of Ra-223. Moreover, we verified the correlation between the BIO-Ra score and treatment completion, which is a well-known prognostic factor in mCRPC patients treated with Ra-223 [ 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…In the present analysis, we verified whether the prognostic power of the BIO-Ra score is still preserved in light of the EMA restriction of the use of Ra-223. Moreover, we verified the correlation between the BIO-Ra score and treatment completion, which is a well-known prognostic factor in mCRPC patients treated with Ra-223 [ 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionsupporting
confidence: 52%
“…This finding is coherent with the observed prediction of treatment completion by the BIO-Ra score in the same time interval. Indeed, several previous studies showed a substantial survival benefit in patients reaching the completion of Ra-223 cycles [ 20 , 21 , 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the self-pay group had lower at baseline serum Hb levels ( p = 0.0036). Buscombe et al 28 reported a median OS of 15 months for patients who completed six cycles of Ra-223 compared to 8 months for patients who completed fewer than six cycles. In the ALSYMPCA trial, the median OS for patients who underwent one to four cycles of Ra-223 was 6.2 months versus 17.9 months for patients who received five to six cycles, indicating that administering four or fewer cycles provides minimal survival benefit.…”
Section: Discussionmentioning
confidence: 99%
“…These results also indicate that radium-223, as appropriate, could be considered as one of the early treatment options integrated into the management of patients with mCRPC, with no apparent adverse impact on long-term prognosis. Other real-world studies have shown correlations between overall survival and completion of 5 or 6 radium-223 injections, use of radium-223 in the first or second line, or use before chemotherapy [11][12][13][14][15][16][17][18]. Patients able to complete the full course of radium-223 injections are likely to have fewer symptoms (including less pain), less disease burden, a good performance status, low baseline PSA and ALP levels, and high baseline hemoglobin levels [11,[19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%